Case report: Robot-assisted laparoscopic partial nephrectomy for renal cell carcinoma in a patient with situs inversus totalis and abdominal cocoon - Zou, Yuhua; Xie, Xiaojuan; Zhong, Cunzhi; Liu, Li; Wang, Qinlin; Yan, Sheng; Zou, Xiaofeng; Liu, Quanliang (Frontiers in Surgery, 2023)
Background: Situs inversus totalis (SIT) is a congenital condition wherein organs in abdominal or thoracic cavity are mirrored from their normal positions. Abdominal cocoon, is a rare disease of unknown aetiology that is characterised by total or partial small intestine encapsulation by a compact fibrocollagenous membrane. Aside from having two extremely rare conditions (SIT and Abdominal cocoon), our patient developed renal cell carcinoma (RCC), which makes this case even more uncommon. Case Presentation: We report the case of a 64-year-old man who was admitted to our hospital with an extremely rare case of localized RCC in the left kidney complicated with SIT and abdominal cocoon. Computer tomography urography (CTU) and angiography (CTA) showed that the patient was confirmed as having SIT, for the space-occupying lesion in the left kidney, clear cell RCC (ccRCC) was considered, the lesion in the right kidney was probably cystic. We diagnosed our patient as having a cT1aN0M0 left RCC, and the RENAL score was 7x. With partial nephrectomy(PN) being the preferred treatment approach, robot-assisted laparoscopic partial nephrectomy (RALPN) was performed after obtaining informed consent. After insertion of the laparoscope, adhesions were observed between the entire colon and the anterior abdominal wall. Then, abdominal cocoon was diagnosed. The surgery was uneventful, and the tumour was resected successfully while preserving the tumour capsule. No intestinal injury or any other complication occurred in the intraoperative or postoperative, and the patient recovered well after the operation. Conclusion: PN is an extremely challenging procedure in patients with SIT and abdominal cocoon. The da Vinci Xi surgical system and thorough preoperative assessment allowed the surgeon to overcome stereotyping, visual inversion, and successfully perform PN in a patient with SIT and abdominal cocoon without increasing the risk of complications and preserving as much renal function as possible. Considering the satisfactory outcomes, this report may hopefully provide a practical reference for the treatment of RCC in patients with other special conditions.